Multiancestry Genome-Wide Association Study of Lipid Levels Incorporating Gene-Alcohol Interactions. Issue 6 (29th January 2019) - de Vries, Paul S; Brown, Michael R; Bentley, Amy R; Sung, Yun J; Winkler, Thomas W; Ntalla, Ioanna; Schwander, Karen; Kraja, Aldi T; Guo, Xiuqing; Franceschini, Nora; Cheng, Ching-Yu; Sim, Xueling; et al.
Abstract: A person's lipid profile is influenced by genetic variants and alcohol consumption, but the contribution of interactions between these exposures has not been studied. We therefore incorporated gene-alcohol interactions into a multiancestry genome-wide association study of levels of high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, and triglycerides. We included 45 studies in stage 1 (genome-wide discovery) and 66 studies in stage 2 (focused follow-up), for a total of 394, 584 individuals from 5 ancestry groups. Analyses covered the period July 2014–November 2017. Genetic main effects and interaction effects were jointly assessed by means of a 2–degrees-of-freedom (df) test, and a 1-df test was used to assess the interaction effects alone. Variants at 495 loci were at least suggestively associated ( P < 1 × 10 −6 ) with lipid levels in stage 1 and were evaluated in stage 2, followed by combined analyses of stage 1 and stage 2. In the combined analysis of stages 1 and 2, a total of 147 independent loci were associated with lipid levels at P < 5 × 10 −8 using 2-df tests, of which 18 were novel. No genome-wide-significant associations were found testing the interaction effect alone. The novel loci included several genes (proprotein convertase subtilisin/kexin type 5 ( PCSK5 ), vascular endothelial growth factor B ( VEGFB ), and apolipoprotein B mRNA editing enzyme, catalytic polypeptide 1 (APOBEC1) complementation factor ( A1CF )) that have a putative role in lipid metabolism on the basis of existing evidence from cellular and experimental models.